The HR answer book : an indispensable guide for managers and human resources professionals - Smith, Shawn A., 1958- (American Management Association, 2004)
Clear answers to the most pressing human resources questions.
Keywords: Personnel management -- Handbooks, manuals, etc.; Human capital -- Handbooks, manuals, etc.; elektronické knihy; electronic books